A study on digital dermatoglyphics among indigenous Assamese populations of Assam - Boruah, Avijit (International Journal of Research in Medical Sciences, 2025)
Background: Dermatoglyphic patterns are among the most distinctive and reliable features of the human body. Their uniqueness plays a vital role in forensic investigations, as no two individuals have identical fingerprints. These patterns also reflect racial, ethnic, and gender differences and can assist in diagnosing certain congenital disorders. Methods: The present study was conducted on 222 students from indigenous Assamese populations, aged 18–22 years, to examine the frequency distribution of fingerprint patterns, identify the most and least prevalent types, and assess inter- and intra-population variations. Fingerprint impressions of both hands were collected and classified using Henry’s classification system. Additionally, pattern intensity index, Dankmeijer’s index, and Furuhata’s index were calculated. Results: The results showed that loops were the most common pattern in both males (58.89%) and females (62.8%). In males, whorls (24.63%) were the second most common, while in females, composites (20.88%) ranked second. Arches were the least common in both sexes—2.41% in males and 7.19% in females. Significant sex-based differences were observed in the distribution of whorls and composites. Among the indices, the pattern intensity index (10.76) and Furuhata’s index (41.82) were higher in males, while Dankmeijer’s index was higher in females (78.84). Conclusions: The study identifies loops as the most common fingerprint pattern and arches as the least common.